PECULIARITIES OF FINANCING SUSTAINABLE DEVELOPMENT GOALS IN MODERN CONDITIONS - MARHASOVA, Viktoriia; POKOTILOVA, Olena; RUZHITSKYI, Yuriy; SHAPOVALOVA, Valentina (Herald of Khmelnytskyi National University. Economic sciences, 2024)
Sustainable development has been identified as a priority for the world’s countries in the near future. However, the Sustainable Development Goals currently face a funding gap. The unequal access to financing for sustainable development, highlighted by the COVID-19 pandemic, has become even more entrenched as the events of 2019-2020 have exacerbated the gap between developed and developing countries. Without urgent action, this financing gap risks becoming a sustainable development gap. The main sources of financing for sustainable development are public spending and foreign investment. The events of 2022 in Ukraine have only exacerbated these concerns. Sharp increases in food and energy prices and rapidly deteriorating financial conditions have further strained the already limited fiscal space in developing countries. The above factors have led to a sharp increase in public spending, which limits the fiscal capacity of both developed and developing countries. This has further implications for the achievement of the Sustainable Development Goals, especially for low-income countries. Today, every third country is at high risk of a fiscal crisis, with not only declining tax revenues but also their share of total GDP. Foreign direct investment can play a crucial role in achieving the Sustainable Development Goals. From the point of view of host countries, it has the potential to enhance growth and innovation, create quality jobs and human capital development, improve living standards and environmental sustainability, etc. The challenge for developing countries in the current scenario is to mobilize sufficient resources from both domestic and international sources not only to achieve the Sustainable Development Goals per se, but also to support people’s livelihoods, health and well-being.